THE ROLE OF PROKARYOTES IN SUBSURFACE WEATHERING OF HYDROTHERMAL SEDIMENTS: A COMBINED GEOCHEMICAL AND MICROBIOLOGICAL INVESTIGATION - Severmann S.; Mills R.A.; Palmer M.R.; Telling J.P.; Cragg B.; Parkes R.J. (My University, 2006)
A detailed geochemical and microbiological study of a ?2 m sediment core from the inactive Alvin mounds within the TAG hydrothermal field was conducted to examine, for the first time, the role of prokaryotes in subsurface weathering of hydrothermal sediments. Results show that there has been substantial post-depositional remobilisation of metal species and diagenetic overprinting of the original high-temperature hydrothermal minerals, and aspects have involved prokaryotic processes. Prokaryotic enumeration demonstrates the presence of a population smaller than the average for deep sea sediments, probably due to the low organic carbon content, but not inhibited by (and hence adapted to) the metal rich environment. There was a small but significant increase in population size associated with the active redox boundary in an upper metal sulphide layer (50-70 cm) around which active metal remobilisation was concentrated (Cu, Au, Cd, Ag, U, Zn and Zn). Hence, subsurface prokaryotes were potentially obtaining energy from metal metabolism in this near surface zone. Close association of numbers of culturable Mn and Fe reducing prokaryotes with subsurface Fe2+ and Mn2+ pore water profiles suggested active prokaryotic metal reduction at depth in core CD102/43 (to ? 175 cm). In addition, a prokaryotic mechanism, which is associated with bacterial sulphate reduction, is invoked to explain the U enrichment on pyrite surfaces and Zn and Pb remobilisation in the upper sediment. Although prokaryotic populations are present throughout this metalliferous sediment, thermodynamic calculations indicated that the inferred low pH of pore waters and the suboxic/anoxic conditions limits the potential energy available from Fe(II) oxidation, which may restrict prokaryotic chemolithotrophic biomass. This suggests that intense prokaryotic Fe oxidation and weathering of seafloor massive sulphide deposits may be restricted to the upper portion of the deposit that is influenced by near neutral pH and oxic seawater unless there is significant subsurface fluid flow. ? 2005 Elsevier Inc. All rights reserved.
Keywords: GEOMICROBIOLOGY; HYDROTHERMAL DEPOSIT; PROKARYOTE; WEATHERING; BACTERIA (MICROORGANISMS); PROKARYOTA